Automation and control remote laboratory: a pedagogical tool - Soares, Filomena (2014)
This paper presents a study to evaluate students' perception of the development and use of remote Control and Automation training kits developed and tested in two Portuguese universities. Three projects were implemented based on real-world environments. The students, supervised by teachers, designed and implemented the kits using the theoretical and practical knowledge taught in traditional classes. The end-user students tested the kits in the course curricular units, operating them either locally or remotely. Successful results were achieved not only in automation and control skills (hard skills) but also in the development of soft skills, leading to encouraging and rewarding goals, inspiring future decisions and promoting synergies in teamwork.